A multiproxy approach to reconstruct the Late Holocene environmental dynamics of the semiarid Andes of central Chile (29°S) - Martel-Cea, Alejandra; Maldonado, Antonio; de Porras, María Eugenia; Muñoz, Praxedes; Maidana, Nora I.; Massaferro, Julieta; Schittek, Karsten (Frontiers in Ecology and Evolution, 2023)
Mountain ecosystems located in the Andes cordillera of central Chile (29-35°S) have been strongly affected by the ongoing Mega Drought since 2010 impacting the snow cover, the surficial water resources (and thereby water storage) as well as the mountain biota and ecosystem services. Paleoenvironmental records in this part of the semiarid Andes are key to estimate the effects of past climate changes on local communities helping to forecast the ecological and biological responses under the aridification trend projected during the 21 st century. Here we present a 2400-years multiproxy paleoenvironmental reconstruction based on pollen, diatoms, chironomids, sedimentological and geochemical data (XRF and ICP-MS data) of Laguna El Calvario (29°S; 3994 m a.s.l), a small and shallow Andean lake. Four main hydrological phases were established based on changes in the lithogenic and geochemical results associated with allochthonous runoff input and the subsequent response of the biological proxies. Between 2400 and 1400 cal yrs BP, wetter than present conditions occurred based on the intense weathering of the lake basin and the dominance of upper Andean vegetation. A decrease in moisture along with sub-centennial discrete wet pulses and lake-level changes occurred until ~800 cal yrs BP followed long-term stable climate conditions between 1850-1950 AD as suggested by a drop of vegetation productivity and low lake levels. Since 1950 AD to the present, a decline in moisture with a severe trend to drier conditions occurring in the last decades occurred as reflected by an upward vegetation belts displacement around Laguna El Calvario along with a turnover of diatom assemblages and high productivity in the water column.